Ethics of digital contact tracing wearables - Schaefer, G. Owen (Journal of medical ethics, 2022)
The success of digital COVID-19 contact tracing requires a strategy that successfully addresses the digital divide—inequitable access to technology such as smartphones. Lack of access both undermines the degree of social benefit achieved by the use of tracing apps, and exacerbates existing social and health inequities because those who lack access are likely to already be disadvantaged. Recently, Singapore has introduced portable tracing wearables (with the same functionality as a contact tracing app) to address the equity gap and promote public health. We argue that governments have an ethical obligation to ensure fair access to the protective benefits of contract tracing during the pandemic and that wearables are an effective way of addressing some important equity issues. The most contentious issues about contact tracing apps have been the potential infringements of privacy and individual liberty, especially where the use of apps or other technology (such as wearables or QR codes) is required for access to certain spaces. Here we argue that wearables, as opposed to apps alone, will make a digital contact tracing mandate more practical and explain some conditions under which such a mandate would be justified. We focus on Singapore as a case study that has recently deployed contact tracing wearables nationally, but also reference debate about wearables in Australia and New Zealand. Our analysis will be relevant to counties trialling similar portable tracing wearables.